Philippines Estradas heir - Journeyman Pictures (United Kingdom : Journeyman Pictures, 2004)
Discussed about president of the Philippines (Estrada) which is a movie star. In Philippines where a third of third of the seats in the national Senate are held by celebrities, fame may be all he needs to succeed.
DVD format
Keywords: Eastrada, Joseph Ejercito; Philippines -- Politics and government -- 1986 -